Intercultural Teaching and Learning English through Reading Skill - Miftakh, Fauzi (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
In this globalization era, teaching English has to also involve intercultural aspects in order that students can develop their awareness towards the differences of the culture of the target language. The intercultural teaching and learning English can be corporated with reading skill activities as suggested by Usó-Juan & Martínez-Flor (2008). This study was a qualitative study which potrayedreading activities to assist intercultural teaching and learning English. The data were taken with observation of teaching learning in the classroom with 25 students of 2nd semester at a state university in Karawang, West Java. 6 students were also selected to have interview in order to know their response and understanding. Finaly, there were some reading activities, such as critical reading and cultural bump, conducted in the classroom that could quite effectively improve the students’ intercultural awareness. Some students also responded by giving positive statements about reading skill activities so their intercultural understanding could improve. However, implementing these activities were not an easy task because the teacher needs to understand the theoritical concept of intercultural language learning.